PENGEMBANGAN APLIKASI ADIBA MSME SEBAGAI PENGHUBUNG LEMBAGA KEUANGAN SYARIAH DENGAN USAHA MIKRO KECIL MENENGAH - Dhina Puspasari Wijaya; Dadang Heksaputra; Ragil Satria Wicaksana; Deden Hardan Gautama (Indonesian Journal of Business Intelligence (IJUBI), 2019)
Islamic banking is one of the icons or representations of Islamic Financial Institutions in Indonesia. Problems around Islamic finance are still a hot topic of discussion. Public participation in the use of financial services is an essential issue on the policy agenda of some developing countries that have underdeveloped banking and commercial systems and often only want to serve high-income customers or large companies, because uneven distribution of financial services will hamper the growth and development of a number of small businesses and poor families. Head of the Sharia Banking Department Ahmad Soekro Tratmono explained that the empirical evidence of the stigma was manifested by the fixed position of the market share of Islamic banking in Indonesia, which from 1992 until now did not exceed the 5 percent limit. Efforts to increase market share in Islamic financial institutions by using information technology. ADIBA MSME is a technology application that aims to map the distribution of the closest LKS institutions that can be accessed by Micro, Small, and Medium Enterprises (MSMEs) entrepreneurs. The existence of ADIBA MSME is expected to be a surefire solution in creating connectivity (Link and Match) between business actors and LKS so that the mobilization of LKS funds becomes more productive, effective, and efficient. With the use of ADIBA MSME technology, it can become an accelerator of regional economic growth through the utilization of Islamic financial literacy so that the use of ADIBA MSME can increase the market share of Islamic financial institutions.